Climate change and the potential distribution of the invasive shrub, leucaena leucocephala (lam.) de wit in Africa (2023)
Leucaena leucocephala, previously known as ‘miracle tree’ because of its numerous agroforestry uses has become a seri¬ous invasive species in tropical regions. Despite the risks associated with the spread of L. leucocephala, changes in its distribution with respect to climate are poorly understood, particularly in Africa where it has been widely introduced in more than 30 countries. To provide first-line information for the management of L. leucocephala, we examined its poten-tial distribution in Africa using ecological niche modelling. We identified bioclimatic variables that determine the global distribution of L. leucocephala, and calibrated niche models using MaxEnt and species occurrences recorded between 1973 and 2013. The potential distribution of this species was estimated from model projections in Africa based on cur¬rent and future climatic conditions. We tested the hypothesis of niche conservatism for L. leucocephala by comparing its climatic niche in Africa to that of its native range. Under current conditions, L. leucocephala is constrained between 30° S and 20° N in Africa, with the broadest distribution in East Africa. High rainfall areas in Central Africa with no known records of this species hitherto, were found to be highly suitable for its establishment. We predicted a significant decre¬ment in the extent of areas at risk of invasion by L. Leucocephala under changing climates in Africa. Our results revealed that the study species occupies a similar but non-identical climatic niche in Africa in relation to its native niche. Climate change is likely to impede the spread of L. leucocephala in Africa.